Intention of Student Behavior Related to the Sustainable Development Goals, Based on the Theory of Planned Behavior [Intención del Comportamiento de Estudiantes Relacionada a Los Objetivos de Desarrollo Sostenible, Basado en la Teoría del Comportamiento Planificado] - Galleguillos-Cortes, C (Universidad Austral de Chile, 2021)
This study aims to determine the intention of future behavior of undergraduate students, concerning the Sustainable Development Goals (SDGs), which is based on the Theory of Planned Behavior. The methodology applied refers to a non-experimental cross-sectional cohort research statistically modeled from structural equations. 213 students from a Chilean Public University were evaluated. The research data were tabulated considering the variables intention, attitude, subjective norm and Perceived Behavioural Control (PBC). The results of the hypothesized model partially support the validity of the Theory of Planned Behavior, that is, the intention of the students determined by the individual beliefs and motivations of the individual. The findings must be understood according to the limitations of the study. Finally, the implications and future lines of research are presented. © 2021
Keywords: educación superior sostenible; sustainable higher education; sustainable university; teoría del comportamiento planificado; theory of planned behavior; universidad sostenible